2012
DOI: 10.1097/spv.0b013e318267c004
|View full text |Cite
|
Sign up to set email alerts
|

Condition-Specific Quality of Life 24 Months After Retropubic and Transobturator Sling Surgery for Stress Urinary Incontinence

Abstract: Aims To compare quality of life (QoL) and factors associated with QoL change after retropubic (RMUS) and transobturator (TMUS) midurethral slings using the Incontinence Impact Questionnaire, (IIQ) and the International Consultation on Incontinence Questionnaire (ICIQ). Methods Five hundred ninety seven women in a multicenter randomized trial of RMUS vs. TMUS were examined. The IIQ and ICIQ were obtained at baseline, 12 and 24 months. Repeated measures analysis of variance tested for differences by treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…We defined the MID as the difference in ICIQ‐UI SF scores between those who were “better” and those who demonstrated “no change”. Since this 25% reduction was arbitrarily chosen, we also analyzed ≥75% reduction in IE on the 7‐day diary . The PGI‐I scale is a self‐rated assessment of change after treatment with seven response levels ranging from “very much worse” to “very much better.” We used the difference in mean ICIQ‐UI SF scores between patients reporting “very much better” and all other responses.…”
Section: Methodsmentioning
confidence: 99%
“…We defined the MID as the difference in ICIQ‐UI SF scores between those who were “better” and those who demonstrated “no change”. Since this 25% reduction was arbitrarily chosen, we also analyzed ≥75% reduction in IE on the 7‐day diary . The PGI‐I scale is a self‐rated assessment of change after treatment with seven response levels ranging from “very much worse” to “very much better.” We used the difference in mean ICIQ‐UI SF scores between patients reporting “very much better” and all other responses.…”
Section: Methodsmentioning
confidence: 99%
“…Bladder perforation was found to be the most commonly reported complication for TVT in studies comparing TVT with TOT [5,14,19]. In addition, our data revealed that TVT had a non-statistically significant higher incidence of UTI and voiding dysfunction (assessed by urine flow test at 24 months).…”
Section: Discussionmentioning
confidence: 50%
“…26 The mean change in the ICIQ after surgery in TOMUS was a decrease of 10.3 (AE5.0). 29 We also assumed an existing rate of depression in the general population to be 18% in developed countries. 1 With a fixed sample size of 526 subjects, the study had >95% power to detect a clinically relevant difference in incontinence-specific quality of life.…”
Section: Ajogorgmentioning
confidence: 99%